2022
DOI: 10.3390/biom12101428
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Crotonylation: An Emerging Player in DNA Damage Response

Abstract: The DNA damage response (DDR) system plays an important role in maintaining genome stability and preventing related diseases. The DDR network comprises many proteins and posttranslational modifications (PTMs) to proteins, which work in a coordinated manner to counteract various genotoxic stresses. Lysine crotonylation (Kcr) is a newly identified PTM occurring in both core histone and non-histone proteins in various organisms. This novel PTM is classified as a reversible acylation modification, which is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Protein crotonylation is emerging as an important player in the regulation of DNA damage signal transduction. Crotonylation generally regulates the functions of DNA repair proteins by modulating protein-protein interactions and DNA binding activities [ 54 ]. For example, RPA1 crotonylation promotes its ssDNA binding ability to facilitating RPA1 recruitment to sites of DNA damage and HR repair [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein crotonylation is emerging as an important player in the regulation of DNA damage signal transduction. Crotonylation generally regulates the functions of DNA repair proteins by modulating protein-protein interactions and DNA binding activities [ 54 ]. For example, RPA1 crotonylation promotes its ssDNA binding ability to facilitating RPA1 recruitment to sites of DNA damage and HR repair [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysine crotonylation (Kcr) is an emerging PTM correlated widely to transcriptional silencing, DSB repair, and DNA replication stress response, the level of which is altered by DNA damage and replication stress [205]. For example, Kcr levels of a series of DSB repair proteins such as RPA1, POLD1, and XRCC5 are upregulated prominently after DNA damage.…”
Section: Dna Damage Repair Modulated By Other Ptmsmentioning
confidence: 99%
“…Accumulating evidence connects this histone mark with proliferation, DNA damage and ageing-associated mechanisms [ 97 100 ]. Histone Kcr were found dysregulated in several cancers, including, stomach, liver, kidney, thyroid, esophagus, colon, pancreas and lung carcinomas [ 97 , 98 ]. In hepatocellular carcinoma (HCC), it was found that high levels of Kcr, induced by the siRNA interference of histone deacetylases (HDACs) or HDAC inhibitors, decrease cancer cell motility and proliferation [ 101 ].…”
Section: Targeting Histone Non-enzymatic Covalent Modificationsmentioning
confidence: 99%